Respuesta :

caylus
Hello,

f(x)=x²/3+x
==>f(6)=6²/3+6=36/2+6=12+6=18

Answer C

Answer:

18

Step-by-step explanation:

Remember to use the order of operations.

First, write 6 wherever there is a X in the original equation. We know to do this because the ''f(6)'' tell us what X is. 6^2 / 3 + 6

Second, we need to find the answer to 6 x 6 or 6 squared. Rember that when you see 6^2, it does not mean 6 x 2. It means that number, times itself. 6 x 6 = 36

Now our equation looks like this. 36 / 3 + 6

Third, we divided 36 by 3. 36 / 3 = 12

Now our equation looks like this. 12 + 6

Finally, we add 12 + 6 together for our final answer. 12 + 6 = 18

ACCESS MORE